Towards enhanced durability: A review of fuel cell electric vehicle development - Chuanxu Luo; Hui Leng Choo; Hafisoh Ahmad; Praveena Nair Sivasankaran (Next Energy)
Fuel cell electric vehicles (FCEVs) provide a viable answer to transportation issues caused by fossil fuel limitations and environmental concerns. This review presents a thorough evaluation of the most recent advances in FCEV durability research. It addresses 4 major topics: component upgrades, technical control techniques, test optimization, and durability prediction. Upgrades to components include improved catalysts, bipolar plates, gas diffusion layers, proton exchange membranes, and plant balancing. Technical control solutions include power, energy, temperature, ventilation, and control management. Stress acceleration and cold start tests are examples of test optimization, whereas durability prediction requires parameter selection, real-time monitoring, dynamic modeling, and lifespan prediction. This review also makes some novel recommendations targeted at improving the endurance of FCEVs. These include measures for raising public awareness, lowering prices while increasing performance, improving subsystems for greater durability, updating health diagnostics to prevent performance deterioration, and implementing supporting regulations to encourage industry upgrading. These findings are expected to accelerate the adoption of FCEVs and the transition to a more sustainable transportation system.